1988
DOI: 10.1017/s0022215100107595
|View full text |Cite
|
Sign up to set email alerts
|

Vascular leiomyoma of the inferior turbinate–report of a case and review of the literature

Abstract: Leiomyoma of the nose and paranasal sinuses is rare. It constitutes about 1 per cent of all benign tumours. This is due to the paucity of smooth muscle in the nose. In this paper, the authors present one case of vascular leiomyoma which arose in the inferior turbinate in a 64-year-old lady. It was treated by partial turbinectomy with the relief of her symptoms of nasal obstruction, epistaxis and facial pain. The English literature on the topic is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
“…1,8,11 At the time of diagnosis, the patients' ages ranged from 25 to 76 years, with an average of 55.6 years. 1,3,7,8,11 Radiologic studies, such as CT scan or MRI do not help much in diagnosis, however it is important to establish the extension of the lesion and treatment planning. 6 Treatment for these tumors is based on local resection, and there are no reports of recurrence after total excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common sites are the uterus and the gastrointestinal tract [2]. It is very rare into the nasal-paranasal cavities (only fifteen cases are reported in the literature) due to the paucity of smooth muscle tissue in this site [3].…”
mentioning
confidence: 99%